The effect of torrefaction pre-treatment on the pyrolysis of corn cobs - Klaas, Matt; Greenhalf, Charles; Ouadi, Miloud; Jahangiri, Hessam; Hornung, Andreas; Briens, Cedric; Berruti, Franco (Results in Engineering, 2020)
Production of green fuels and chemicals from non-edible corn cob residues presents an excellent opportunity to produce sustainable low carbon energy vectors as an alternative to fossil fuels. The objective of this study was to optimize the fuel physical and chemical properties of torrefied corn cobs bio-oil by investigating the relationship between feedstock pre-treatment (torrefaction) temperatures (240, 260, 280 and 300 ​°C), and subsequent pyrolysis temperatures (400, 450, 500 and 550 ​°C). This experimental methodology aimed to improve both yields and properties of bio-oils from corn cobs. Torrefaction was first carried out as a pre-treatment step using a custom-built torrefaction reactor followed by pyrolysis using a continuous fluidized bed reactor. Torrefaction was found to be a promising pre-treatment step because it had the effect of reducing the water content and viscosity within the bio-oil. Corn cobs grinding energy requirements could be reduced by 69% when torrefaction was applied from 240 ​°C to 260 ​°C. A maximum bio-oil yield of 51.7% was achieved when the optimal temperatures (torrefaction 260 ​°C and pyrolysis 450 ​°C) was applied. Overall, using torrefaction as a pre-treatment step before pyrolysis was shown to be a promising approach for improving some physiochemical properties of bio-oil for its application as a fuel.
CRIS-Team Scopus Importer:2020-09-11
Keywords: Bio-oil; Corn cobs; Grinding energy; Pyrolysis; Torrefaction